The Implementation of Iqab for Islamic Boarding School Students - Rani Nurisa Tanjung; Syamsu Nahar; Fibri Rakhmawati (Universitas Pahlawan Tuanku Tambusai, 2023)
The implementation of rules in the classroom, including the imposition of punishment (iqab), can help students develop their personalities. In this study, the 'iqab program for elementary school children at the Darul Hikmah Islamic boarding school, Asahan Regency, will be described. A qualitative methodology and phenomenological approach are used in this investigation. employing observation, interviews, and documentation studies to gather data. data analysis that includes data display, data reduction strategies, and conclusion-making. The findings of this study show that: (1) the academic guidebook for pupils serves to socialize the idea of the